2022
DOI: 10.1016/j.omtm.2021.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular RNase activity dampens zinc finger nuclease-mediated gene editing in hematopoietic stem and progenitor cells

Abstract: Over the past decade, numerous gene-editing platforms which alter host DNA in a highly specific and targeted fashion have been described. Two notable examples are zinc finger nucleases (ZFNs), the first gene-editing platform to be tested in clinical trials, and more recently, CRISPR/Cas9. Although CRISPR/Cas9 approaches have become arguably the most popular platform in the field, the therapeutic advantages and disadvantages of each strategy are only beginning to emerge. We have established a nonhuman primate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Furthermore, RNase activities in the monocyte lysate is significantly higher (~5-fold) than in the T cell lysate ( Figure 3 B). Moreover, a pan-RNase inhibitor was recently reported to allow higher mRNA expression and enhanced mRNA-based genome engineering in non-human primate hematopoietic cells [ 48 ]. Thus, we hypothesized that electroporating heterologous mRNA/sgRNAs into the cytoplasm may activate or be subject to mRNA restriction mechanisms in monocytes, leading to a degradation or inhibition of heterologous mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, RNase activities in the monocyte lysate is significantly higher (~5-fold) than in the T cell lysate ( Figure 3 B). Moreover, a pan-RNase inhibitor was recently reported to allow higher mRNA expression and enhanced mRNA-based genome engineering in non-human primate hematopoietic cells [ 48 ]. Thus, we hypothesized that electroporating heterologous mRNA/sgRNAs into the cytoplasm may activate or be subject to mRNA restriction mechanisms in monocytes, leading to a degradation or inhibition of heterologous mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these observations indicate that members of RNase A superfamily in monocytes may be responsible for inefficient and inconsistent mRNA-based genome editing. Similarly, Peterson and Venkataraman et al (2021) demonstrated that intracellular RNases were responsible for poor mRNA expression and introducing RNase inhibitor along with mRNA-based engineering platforms allowed for higher engineering efficiencies in non-human primate hematopoietic stem cells [ 48 ]. In addition, we demonstrate the use of a mRNA encoding base editor for multiplex genome editing, allowing for safe, multiplex genome modification without risks associated with DSBs, i.e., DNA damage response, chromosomal loss, or translocations.…”
Section: Discussionmentioning
confidence: 99%
“…https://doi.org/10.1038/s41551-023-01026-0 tripled or quadrupled the total volume of all RNAs added per electroporation beyond the manufacturer's suggestion. Finally, we tested the addition of RNasin, which has been previously reported to increase the efficiency of RNA-based electroporations by inhibiting endogenous RNase activity 35 (Fig. 2c).…”
Section: Articlementioning
confidence: 99%
“…Although studies have demonstrated transcriptional changes in HSPCs in response to electroporation, its impact on stemness and functional activity is minimal ( Cromer et al, 2018 ). Numerous electroporation devices, including the Lonza 4D-Nucleofector, the MaxCyte electroporation system, the Neon electroporation system, and the Harvard Apparatus/BTX ECM600 Electro Cell Manipulator/apparatus, are currently being used for HSPC gene editing ( Vakulskas et al, 2018 ; Métais et al, 2019 ; Frangoul et al, 2021 ; Magis et al, 2022 ; Peterson et al, 2022 ). More importantly, ongoing gene editing-based clinical trials are using electroporation to deliver ZFNs, Cas9, and Cas12a nucleases and ABEs into HSPCs ( Table 2 ).…”
Section: Introductionmentioning
confidence: 99%